Effect of framework type on survival probability of implant-supported temporary crowns: An in vitro study - Rodrigues, Vinícius-Anéas; Dal Piva, Amanda-Maria-de Oliveira [UNESP]; Yamaguchi, Claudio-Akira; Borges, Alexandre-Luiz-Souto [UNESP]; Mukai, Marcio-Katsuyoshi; Tribst, João-Paulo-Mendes [UNESP] (Medicina Oral, S.L., 2020)
Background: This in vitro study evaluated the effect of framework type on the survival probability of temporary implant-supported crowns and on the implant platform structure after dynamic fatigue. Material and Methods: Thirty (30) external hexagon implants (3.75 x 10 mm) were embedded in acrylic resin following the ISO-14801. Standardized temporary crowns (n=10, N=30) were manufactured in acrylic resin and divided according to the framework type: Total plastic, Plastic with CoCr base and Titanium. The crowns were installed onto the implants (20N. cm) and fatigued (100N, 2 Hz) to determine the crowns' survival probability for missions of 300.000 and 600.000 cycles. Fatigue data were submitted to the Kaplan-Meier test followed by Wilcoxon and Log Rank, all with α = 5%. The implant platforms were parametrically inspected based on the scanning before and after the fatigue to evaluate the damage. The strain values were analyzed using One-way ANOVA and Tukey test, all with α = 5%. Results: ANOVA revealed that the Total plastic showed less implant damage (-0.07 ±-0.03 mm) than the Plastic with CoCr base (-0.08 ±-0.04 mm) and the Titanium (-0.10 ±-0.01 mm) frameworks. Therefore, the framework type to manufacture implant-supported temporary crowns influences the fatigue survival of the restoration and the implant platform damage. The Plastic with CoCr base and Titanium frameworks showed superior reliability than the Total plastic framework which could not survive 600,000 cycles. Conclusions: The Plastic with CoCr base and the Titanium framework are suitable for restorations over 3 months in use, without a difference in the implant platform damage.
Keywords: Axial loading; Implant dentistry; Methodological study; Occlusion